Impact of Soybean Nodulation Phenotypes and Nitrogen Fertilizer Levels on the Rhizosphere Bacterial Community - Wang, Hao; Gu, Chuntao; Liu, Xiaofeng; Yang, Chunwei; Li, Wenbin; Wang, Shaodong (Frontiers in Microbiology, 2020)
To determine the effects of nodulation phenotypes and available nitrogen levels on bacterial communities in the rhizospheres of soybean plants. High-throughput sequencing of the 16S rRNA gene (16S rDNA) was performed to estimate the bacterial community in rhizospheres of three soybean lines (the super-nodulating line Dongfu 4, the non-nodulating line En 1282 and the wild-type nodulating line Heihe 38) grown in soil supplied with different levels of N-fertilizer. The results revealed the following: 1) Both the soybean cultivar and the N-level affected the rhizosphere bacteria community, but the nodulation phenotypes contributed more than the N-supply. 2) Super-nodulating phenotypes decreased the diversity of rhizoshpere bacteria and its rhizoshpere bacterial community composition was not considerably affected by N level. 3) The response of bacterial communities to the soil available nitrogen was different in the three nodulation phenotypes of soybean, and it was enhanced with the increase of nitrogen levels for the wild type soybean samples. 4) Bradyrhizobium in rhizosphere were positively correlated with nodule number and negatively correlated to available nitrogen; while the Burkholderia was positively correlated with nodule mass and ethylene production, Dyella was positively correlated with nodule number as well as nodule mass and ethylene production.